Penerapan Algoritma C4.5 Seleksi Penerima Beasiswa Bidikmisi Pada Kampus Stmik Agamua Wamena - WILYAM ARIESTA HALUK; Syafruddin Syarif; Supriadi Sahibu (Journal Teknik Dan Teknologi, 2025)
Bidikmisi Scholarship is a financial aid program aimed at economically disadvantaged students with strong academic performance. The selection process for recipients of this scholarship often faces challenges, particularly in determining the eligibility of candidates, which requires numerous criteria and complex data analysis. This study aims to develop a scholarship selection system using the C4.5 algorithm. It is expected that this algorithm can automate and expedite the selection process with more transparent and objective results. The dataset used includes applicants for the Bidikmisi scholarship from 2015 to 2020. The methods applied include oversampling and undersampling techniques to address class imbalance in the data. Based on testing, this system achieved an accuracy of 76%, with a precision of 76% and recall of 71%, indicating that the system can be relied upon for the scholarship selection process at STMIK Agamua Wamena.